(untitled) (Research, Society and Development, 2022)
Infectious diseases that affect the respiratory tract manifest themselves in an acute and chronic form, highlighting in this study Chronic Obstructive Pulmonary Disease (COPD), Pneumonia, Asthma and Tuberculosis. In the world, respiratory diseases are considered important causes of illness and death, affecting children, adults and the elderly. With this study, we aim to identify the incidence of deaths from respiratory tract diseases in the city of Porto Velho, analyzing the Death Certificate (D.O) between the years 2017 and 2018. Being a quantitative descriptive study, based on the electronic system of the Ministry of Health, and the Notifiable Diseases Information System (SINAN). The collected data were analyzed, tabulated in Microsoft Office Excel ® spreadsheets and the percentage of each response was calculated for each of the variables obtained and the means were graphically compared using standard deviation bars. It was observed that, among the respiratory tract diseases addressed, most of the deaths occurred among males, whose age group includes middle-aged adults (40-60 years) and the elderly, with elementary school I being the main level of schooling and the hospital environment the place of highest incidence. Through this research, we present an epidemiological profile of deaths from respiratory diseases in Porto Velho. Based on the results and analyzes carried out, propositions are offered regarding the care of patients with respiratory tract disease, educational promotions in health and improvement of records and data collection regarding these conditions.